Continuously Variable Regulation of the Speed of Bubble‐Propelled Janus Microcapsule Motors Based on Salt‐Responsive Polyelectrolyte Brushes. Issue 14 (16th January 2019) - Ji, Yuxing; Lin, Xiankun; Wang, Daolin; Zhou, Chang; Wu, Yingjie; He, Qiang
Abstract: The engineering of self‐propelled micro‐/nanomotors (MNMs) with continuously variable speeds, akin to macroscopic automobiles equipped with a continuously variable transmission, is still a huge challenge. Herein, after grafting with salt‐responsive poly[2‐(methacryloyloxy)ethyltrimethylammonium chloride] (PMETAC) brushes, bubble‐propelled Janus microcapsule motors with polyelectrolyte multilayers exhibited adjustable speeds when the type and concentration of the counterion was changed. Reversible switching between low‐ and high‐speed states was achieved by modulating the PMETAC brushes between hydrophobic and hydrophilic configurations by ion exchange with ClO4 − and polyphosphate anions. This continuously variable regulation enabled control of the speed in an accurate and predictable manner and an autonomous response to the local chemical environment. This study suggests that the integration of polymer brushes with precisely adjustable responsiveness offers a promising route for motion control of smart MNMs that act like their counterparts in living systems. Abstract : A micromotor with a gearbox : The continuously variable speed regulation of micromotors has been achieved by grafting salt‐responsive poly[2‐(methacryloyloxy)ethyltrimethylammonium chloride] (PMETAC) brushes onto bubble‐propelled Janus microcapsule motors. Adjustment of the wetting properties of PMETAC brushes by counterion exchange modulates the speed in an accurate and predictable manner and allows transitions from high to low speeds (see figure).